PERAN MEDIA AUDIO VISUAL BERBASIS HOTS DALAM PEMBELAJARAN DI SD NEGERI DAYA II - Astriani, Astriani; Syam, Nur (ALENA : Journal of Elementary Education, 2023)
This study aims to determine the role of hots-based learning media in the independent perspective of learning for fifth grade students at SD Negeri Daya II Makassar City. This study uses a qualitative approach, with a qualitative descriptive research type. The objects of this research were students and teachers of class V SD Negeri Daya II Makassar City. Sources of data in this study are observation, interviews and documentation. The data in this study were analyzed using 3 stages, namely data reduction (data reduction), data display (data presentation), conclusion drawing (conclusion), and verification (verification). The results of the research conducted showed that: (1) the role of hots-based audio-visual learning media in the perspective of independent learning has an important role for success in students. With the use of audio visual media students are more motivated to learn. This is evident from the fact that learning is more interesting and easy to understand, the classroom atmosphere becomes more conducive and students' attitudes become happy, not bored, enthusiastic and enthusiastic in the learning process and students' attention is focused on the topics discussed in learning and arouses students' understanding contained in the the value of the daily test results and students can repeat the learning material. (2) the supporting and inhibiting factors for the application of audio-visual media are: the supporting factors are the existence of adequate facilities and infrastructure, students are happier when using learning media. While the inhibiting factors are the power outages when using the media, there are students who are noisy and passing by when the learning process is in progress. The implementation of audio-visual media in this lesson can encourage students' enthusiasm and curiosity about the lesson, so that students are expected to easily understand the material being taught.